Development of a nurses’ situation awareness scale for clinical deterioration: a methodological study - Hye Jin Kang; Yi Kyung Ha (Journal of Korean Academy of Nursing, 2026)
Purpose: This study aimed to develop a scale for assessing nurses’ situation awareness of clinical deterioration and to evaluate its validity and reliability.Methods: This methodological study followed the scale-development guidelines of DeVellis and Thorpe. Item generation began with 44 items derived from 17 attributes identified through a hybrid-model concept analysis, which included a literature review and focus group interviews with 13 nursing experts. After content validity was evaluated by seven experts, 30 items were retained. A pilot test was then conducted with 20 hospital nurses to assess item comprehensibility. From August 30 to October 6, 2025, a total of 446 hospital nurses participated in the survey, and data from 440 respondents were analyzed. Construct validity was examined using exploratory and confirmatory factor analyses, along with convergent and discriminant validity testing. Internal consistency was evaluated using Cronbach’s α and McDonald’s ω.Results: Exploratory factor analysis yielded a three-factor model, which showed acceptable fit in confirmatory factor analysis. The final instrument comprised 24 items across three factors, was scored on a 5-point Likert scale, and was named the Nurses’ Situation Awareness Scale for Clinical Deterioration (NSAS-CD). The scale showed high internal consistency, with Cronbach’s α of .98 and McDonald’s ω of .98.Conclusion: The NSAS-CD demonstrated acceptable validity and reliability for assessing nurses’ situation awareness of clinical deterioration. Further research is needed to evaluate its generalizability across diverse clinical settings and to establish standardized criteria for clinical deterioration.